Language and Social Culture in the Technological World - Shalaw Sulaiman Abdlurahman; Kawar Mohammed Sanaadin (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Language changes occur due to changes in cultural, political, and technological revolutions taking place around the globe. The central aspect that every government and nation is implementing containment measures is the local language and culture against the changes that are taking place around the world. Although, despite the proactive effort put in place, the language changes are unavoidable. Therefore, governments and nations should formulate other ways to integrate the new changes in language with the existing language without losing its authenticity. Industrial and cultural evolution has played a fundamental role in language change. Other factors that have led to language evolution include political, cultural relations and economic, geographical aspects, and military conflict. These language evolutions are systemic since the changes don’t occur irregularly or accidentally. Systematic language evolution is a section of language identification, making it part and parcel of human identification. Despite the external factors that cause language changes, other natural factors contribute to language change based on the needs of society. The unique aspect of language evolution is that the changes gradually occur; therefore, it will take several years to acknowledge language changes fully. The technological development that is taking place around the globe is associated with providing technical and scientific instruments, which in return are greatly influencing changes that are being witnessed in language. The technical and scientific instruments have a more significant impact on the language changes because of their ability to penetrate the global market using their commercial identity.